A pseudo-3D model with 3D accuracy and 2D cost for the CFD–PBM simulation of a pilot-scale rotating disc contactor. (12th January 2016) - Chen, Hang; Sun, Ze; Song, Xingfu; Yu, Jianguo
Abstract: In this study, the computational fluid dynamics–population balance model (CFD–PBM) was developed for a five-compartment pilot-scale rotating disc contactor (RDC) using the solving methods of finite volume method (FVM) and quadrature method of moments (QMOM) as implemented in Fluent 14.0 . The differences between a simplified two-dimensional (2D) axisymmetric swirl model and a full three-dimensional (3D) model were investigated, and a pseudo-three-dimensional (pseudo-3D) model was developed to combine the benefits of both the 2D and 3D frameworks. The comparison results of the velocity distributions, droplet mean diameter and turbulent dissipation rate indicated that the 3D approach was suitable for quantitative investigations, whereas the 2D axisymmetric swirl model had only qualitative predictive capabilities. The differences are probably attributed to the 2D framework ignoring the cylindrical geometry characteristics of the problem. Based on this knowledge, a pseudo-3D model was proposed by constructing a fan-shaped geometry to overcome this disadvantage, and a parametric study was conducted to determine the angle of the sector. The results showed that the pseudo-3D model had nearly the same computational accuracy as the full 3D simulation, which verified the approach. Moreover, the sector angle had almost no effect on the simulated results, and only two layers of grids in the tangential direction were sufficient. Thus, the pseudo-3D model was found to be a powerful tool with computational costs approximate to those of the 2D framework, but with a calculation accuracy near that of the 3D model. Highlights: The differences between 2D and 3D CFD–PBM simulations were discussed for a pilot RDC. The geometrical deviation was thought to be the main reason for the differences. A pseudo-3D model was developed to combine the benefits of both the 2D and 3D models.